Social inequalities and periodontal disease: multilevel approach in SBBrasil 2010 survey - Vettore, Mario Vianna; Marques, Regina Auxiliadora de Amorim; Peres, Marco A (Revista de Saúde Pública, 2013)
OBJECTIVE: To estimate the prevalence and geographical distribution of periodontal disease in the Brazilian adult population and its associations with contextual and individual social inequalities. METHODS: Data from adults aged 35 to 44 who participated in the 2010 Brazilian Brazilian Oral Health Survey (SBBrasil 2010) (n = 9,564) were used. The Community Periodontal Index (CPI) and clinical attachment loss (CAL) were used to define “moderate to severe” periodontal disease (CPI >; 2 and CAL >; 0) and “severe” periodontal disease (CPI >; 2 and CAL >; 1). Contextual social inequalities assessed were Human Development Index and income inequalitiy (Gini Index). Other contextual variables were integration of oral health teams in the Family Health Programme and the percentage of adult smokers. Multilevel logistic regression models for participants with complete data (n = 4,594) were used to estimate odds ratios (OR) and 95% confidence intervals (95%CI) between social inequalities and periodontal disease. RESULTS: The prevalence of “moderate to severe” and “severe” periodontal disease in Brazilian adults was 15.3% and 5.8%, respectively, with considerable variation across municipalities. Of the contextual variables, income inequality was independently associated with “severe” periodontal disease (OR = 3.0, 95%CI 1.5;5.9). Lower oral health teams coverage was associated with both definitions of periodontal disease whereas the percentage of smokers remained associated with “moderate to severe” periodontal disease. Older adults, brown skin color, males and those with lower family income and less schooling were more likely to both periodontal conditions. CONCLUSIONS: In Brazil, the prevalence of periodontal disease varied across the municipalities and according to definition of periodontal disease. Income inequality played a significant role in the occurrence of “severe” periodontal disease. Individual characteristics of social position were associated with both forms of periodontal disease.